The Influence of Motivation and Competences on Amil’s Work Productivity at the National Amil Zakat Institution Dompet Dhuafa - Fatimah, Rina; Pancasasti, Ranthy (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Zakat is an important instrument in efforts to eradicate poverty in society. Dompet Dhuafa has implemented a fundraising strategy through technology aimed at increasing the collection of zakat funds. Increasing zakat collection needs to be balanced with the ability to distribute zakat funds and readiness to face potential risks. Amil's work productivity is needed to be able to collect large amounts of zakat funds and at the same time be able to distribute zakat funds. This research aims to analyze the influence of work motivation and amil's competence on amil's work productivity at LAZNAS Dompet Dhuafa. This research uses a quantitative-descriptive approach. Respondents in this study were 75 people using simple random sampling techniques. Data was collected through filling out questionnaires by respondents. The results of the research show that the processing indicators influence the test using PLS-SEM (Structural Equation Model). The results of the research show that the indicators which have the highest average score on each variable include the need for affiliation on the work motivation variable, spiritual competence on the amil competence variable, and ability and improving the results achieved on the work productivity variable, test results of the model of the influence of work motivation and Amil's competence on work productivity shows an R-Square figure of 0.47 while the remaining 0.53 is influenced by other factors not examined in this research. Another finding from the influence test results is that the amil competency coefficient has a significant direct influence of 0.655. This shows that the better the amil's competence, the higher the work productivity produced by the amil. This research has limitations in the variables studied and the number of respondents. This research has high originality because it is in accordance with the challenges faced by national zakat institutions today.   Keywords: Amil Zakat, Motivation, Competence, Work Productivity